Posterior Segment Pathologies in Leprosy Patients with Visual Impairment: A Case Series - Gitalisa Andayani Adriono; Andi Marsa Nadhira; King Hans Kurnia; Yunia Irawati (eJournal Kedokteran Indonesia, 2022)
Leprosy is an important infectious disease, which is still prevalent in developing countries including  Indonesia. This disease may affect the skin, extremities, peripheral nerves, and the eyes, causing disabilities of the patient. Leprosy is known to cause various ocular disorders, however, posterior segment abnormalities which involve the retina, choroid dan vitreous, have rarely been reported. Therefore, we present a case series of patients with posterior segment pathologies in visually impaired leprosy patients. These patients were identified during a community-based screening program on 99 leprosy patients, held in July 2019 in Alverno Hospital, Singkawang West Kalimantan. Patient comprised of inpatients and former patients who lived within the city and nearby cities who were invited for the program. All patients underwent comprehensive ophthalmology examination, performed by general ophthalmologists. Visual impairment was found in 15 patients, and their pupils were dilated, followed with posterior segment examination with indirect ophthalmoscopy and fundus photograph, using a handheld fundus camera, done by a vitreoretina specialist. Out of all patients screened, we did not find any leprosy-related posterior segment abnormalities. However, posterior segment pathologies were found in six patients, including peripapillary atrophy, myopic crescent, drusen and chorioretinal atrophy. One patient showed extensive chorioretinal atrophy with pigment clumping, which may be caused by leprosy- related chronic inflammatory process.